Subjective Measures in Sit-to-Stand Task in Post-Stroke Hemiparesis: Comment on Brière, Nadeau, Lauzière, and Gravel (2013). Issue 2 (October 2014) - Ng, Annie W. Y.; Chan, Alan H. S.
In a recent study, Brière, Nadeau, Lauzière, and Gravel (2013) examined the perceptions of individuals post-stroke on their weight-bearing distribution and knee effort distribution in sit-to-stand tasks. The present comment emphasized the importance of the feeling of post-stroke hemiparesis in sit-to-stand task and identified areas of improvements of the target study.